Controle de reativos utilizando geradores de indução de dupla alimentação (DFIG) na melhoria da estabilidade do sistema elétrico de potência - Silva Júnior, Guilherme Penha da (2017)
This work proposes an analysis of the transitory stability impact on the power grid, with wind power integration, as this source is intermitent and has low inertia. Therefore, some disturbs are generated on the power system in order to do a better analysis, the disturbs are: sudden removal of load, abrupt variation of wind and a symmetric short on a power bar. The whole analysis is done by computacional simulations using the Matlab software. Lastly, to mitigate the damages to the system some control techniques are implemented in the Double Fed Induction Generator (DFIG) in order to inject reactive power to control the voltage. The results support the behaviour of the proposed system and the efficacy of the control technique to attenuate the sudden variations on the system bar voltage level, thereby increasing the reliability and quality of the power system. Further investigations are proposed, in order to validate the concerns caused by the wind power integration into the power system, comparisons are made (with and without the presence of the wind farm) in the levels of currents, in the angular speed, in the active and reactive power generation over all the generations bars of the system.